Composites with clay and bentonite matrix: a study of the certain materials behavior for ceramic composites - Matei, Simona Corina; Varga, Bela; Bedo, Tibor; Pop, Mihai Alin; Stoicănescu, Maria; Crișan, Aurel (Elsevier BV, 2019)
The paper is a study regarding ceramic matrix composites with clay and bentonite. Ceramic powders (Al2O3 and SiC) and metallic particles (Cu, Al and Fe) were used as reinforcement. The materials used for the matrix were first subjected to a thermal analysis. Based on the obtained information from the thermal analysis, the methodology for making the composites was established, namely the mixing of the dry components for a good homogenization, cold pressing for compacting in cylindrical samples and finally sintering at the appropriate temperatures. In this way cylindrical specimens (diameter between 15-16 mm and height between 11-15 mm) were made. For composite materials, the porosity and compressive strength are important parameters that depend on the individual behaviour of the sintering phases, but also on the interactions between the phases at high temperatures [1]. Reinforcing materials were added in composites in two steps. Firstly, clay and bentonite matrix composites with ceramic powders (Al2O3 and SiC) were first obtained and analysed, following the effect of these ceramic powders on the properties. Secondly, for each type of composite (with a certain matrix or a certain reinforcement material), metal powders of Al, Cu and Fe (10%) were introduced, again looking at the effect of the ceramic powders as materials of reinforcement on the properties of composites. The study found a significantly different behaviour after the addition of ceramic powders. At the same time, if in the case of composites reinforced only with ceramic powders, the increase in the proportion of powders leads to a decrease in compressive strength, the addition of metal powders radically changes this type of dependence, their compressive strength increasing with the proportion of ceramic reinforcement powders. The behaviour of bentonite matrix composites has always been superior to those of clay matrix, for the same types and proportions of reinforcement materials. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: porosity; metallic particles; thermal analysis; bentonite; ceramic composites